Review: The Monster in the Garden by Luke Morgan - Flattun, John-Wilhelm (Early Modern Culture Online, 2018)
Review of The Monster in the Garden: The Grotesque and the Gigantic in Renaissance Landscape Design, by Luke Morgan. U Penn Press, 2016.